Padronização de metodologia para identificação molecular de Pipper yellow mottle virus (PYMoV) em plantas de pimenta-do-reino cultivadas no norte do Espírito Santo - Rocha, Anna Caroline Brinco (2017)
Black pepper is one of the most commercialized spices in Brazil, and the state of Espírito Santo is considered the second largest producer of this delicacy. There are problems with the spread of viral diseases since pepper is marketed by cuttings and / or cuttings. Both in Brazil and in the state of Espírito Santo have already been reported the presence of Piper yellow mottle virus (PYMoV). The objective of this subproject was to standardize a virus detection methodology through young leaves of iv Bragantina pepper. For this, different methods of DNA extraction using symptomatic sheets and asymptomatic sheets and different protocols to adapt the PCR (Polymerase chain reaction) test using specific primers to amplify the DNA fragment of the PYMoV virus were tested. PCR results were analyzed by agarose gel electrophoresis stained with GelRed or Blue Juice. Since it was not obtained bands of specific fragments of the PYMoV, because the primers used amplifacaram nonspecific bands.